2006
DOI: 10.1037/0735-7044.120.4.852
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the dorsal hippocampus or parietal cortex differentially affect spatial information processing.

Abstract: The present experiments used 2 versions of a modified Hebb-Williams maze to test the role of the dorsal hippocampus (dHip) and parietal cortex (PC) in processing allocentric and egocentric space during acquisition and retention. Bilateral lesions were made to either the dHip or PC before maze testing (acquisition) or after maze testing (retention). The results indicate that lesions of the dHip impair allocentric maze acquisition, whereas lesions of the PC impair egocentric maze acquisition. During retention, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Each tetrode consisted of four polyimide-coated, nichrome wires (14 m diameter) twisted together. The hyperdrives were positioned over the PPC (centered 4.5 mm posterior from bregma and Ϯ2.95 mm from midline) to target the average PPC region based on connectivity (Kolb and Walkey, 1987;Reep et al, 1994;Torrealba and Valdes, 2008;Calton and Taube, 2009) and studies designed to characterize PPC contributions to navigation (Kolb and Walkey, 1987;Chen et al, 1994a;Rogers and Kesner, 2006;Calton and Taube, 2009); though slightly more posterior regions are included compared with the most recent recording studies (Nitz, 2006(Nitz, , 2012Whitlock et al, 2008Whitlock et al, , 2012 due to an emphasis on the PPC region shown to encode allocentric (world centered) auditory cue position (Nakamura, 1999). Our recording coordinates are likely to correspond to the intersection of the mouse anteromedial, posteromedial, and mediomedial areas (Wang and Burkhalter, 2007;Wang et al, 2012).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Each tetrode consisted of four polyimide-coated, nichrome wires (14 m diameter) twisted together. The hyperdrives were positioned over the PPC (centered 4.5 mm posterior from bregma and Ϯ2.95 mm from midline) to target the average PPC region based on connectivity (Kolb and Walkey, 1987;Reep et al, 1994;Torrealba and Valdes, 2008;Calton and Taube, 2009) and studies designed to characterize PPC contributions to navigation (Kolb and Walkey, 1987;Chen et al, 1994a;Rogers and Kesner, 2006;Calton and Taube, 2009); though slightly more posterior regions are included compared with the most recent recording studies (Nitz, 2006(Nitz, , 2012Whitlock et al, 2008Whitlock et al, , 2012 due to an emphasis on the PPC region shown to encode allocentric (world centered) auditory cue position (Nakamura, 1999). Our recording coordinates are likely to correspond to the intersection of the mouse anteromedial, posteromedial, and mediomedial areas (Wang and Burkhalter, 2007;Wang et al, 2012).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Humans and other animals employ egocentric strategies regularly in a variety of spatial environments. However, since egocentric capacities are not dependent on the integrity of the hippocampal formation (Eichenbaum et al, 1990;Rogers & Kesner, 2006;Weniger & Irle, 2006;Weniger et al, 2009), it is critical to prevent subjects from using egocentric strategies when using allocentric spatial capacities as an assay for hippocampal function (Banta Lavenex & Lavenex, 2009). In our paradigm, the use of four different entrance points and multiple potential reward locations precludes children from using egocentric strategies.…”
Section: Task Specificitymentioning
confidence: 99%
“…Allocentric spatial memory, the memory for locations coded in a relational manner to the surrounding environment, is a fundamental component of episodic memory, the ''where'' component of the defining ''what, where and when'' of episodic memories (Nyberg et al, 1996;Tulving, 2002). Like semantic and episodic memory, allocentric spatial memory is also dependent on the integrity and function of the hippocampus in adult individuals (Banta Lavenex, Amaral, & Lavenex, 2006;Morris, Garrud, Rawlins, & O'Keefe, 1982;O'Keefe and Nadel, 1978;Olton, Walker, & Gage, 1978;Place et al, 2012; for a review of the theory of the general relational nature of the hippocampus, see Konkel & Cohen, 2009), whereas egocentric spatial memory, the memory for locations coded in relation to the body such as ''on my left'', ''on my right'' or ''in front of me'', is not (Banta Lavenex & Lavenex, 2009;Eichenbaum, Stewart, & Morris, 1990;Rogers & Kesner, 2006;Weniger & Irle, 2006;Weniger, Ruhleder, Wolf, Lange, & Irle, 2009). However, despite our ever-increasing comprehension of the role that the hippocampal formation serves in learning and memory in adult individuals, our understanding of how different memory systems develop and why different types of hippocampus-dependent memory emerge when they do in early childhood is much less complete (see Bauer, 2007;Newcombe et al, 2007 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…The posterior parietal cortex com putes spatial relationships in two reference frames: a topological refe rence frame with reference to the local cue configurations irrespective to the distal cue configurations as well as in the egocentric frame of ref erence, primarily in reference to the sagittal midline of the individual, but also to single landmarks or beacons in the environment [74][75][76] Figure 1 with particular focus on the contributions from the hip pocampus. Spatial relationships among stimuli are defined mathematically in terms of raw angles and distanced from the rat.…”
Section: Knowledge-based Spatial Memory Processesmentioning
confidence: 99%